Women Political Participation in Peacebuilding in Southern Thailand - Marddent, Amporn (Al-Albab, 2017)
This article explores the historical, practical and consequences of women in political participation in the peace process during the ongoing conflict negotiations from 2004 until the present time. The author examines the cases of the Malay Muslims, who are the dominated populations in this violent conflict region and a significant minority group in Thailand, and the non-Malays who are also active in paving the way for peace making in various forms of activity in southern border provinces of country. Gender analysis of the intertwined ethno-religious and political identities of the Malays and non-Malays demands a need to reorientation of the concept of peace and security which contributed to illuminate deeply understanding of the society during conflict resolution.